Milk Street : the new rules : recipes that will change the way you cook - Kimball, Christopher (Voracious, Little, Brown and Company, 2019)
This revelatory new book from James Beard Award-winning author Christopher Kimball defines 75 new rules of cooking that will dramatically simplify your time in the kitchen and improve your results. These powerful principles appear in more than 200 recipes that teach you how to make your food more delicious and interesting, like: *Charred Broccoli with Japanese-Style Toasted Sesame Sauce (Rule No. 9: Beat Bitterness by Charring) *Lentils with Swiss Chard and Pomegranate Molasses (Rule No. 18: Don't Let Neutral Ingredients Stand Alone) *Bucatini Pasta with Cherry Tomatoes and Fresh Sage (Rule No. 23: Get Bigger Flavor from Supermarket Tomatoes) *Soft-Cooked Eggs with Coconut, Tomatoes, and Spinach (Rule No. 39: Steam, Don't Boil, Your Eggs) *Pan-Seared Salmon with Red Chili-Walnut Sauce (Rule No. 44: Stick with Single-Sided Searing) *Curry-Coconut Pot Roast (Rule No. 67: Use Less Liquid for More Flavor).